A Secondary Current Distribution In A Zinc Electrowinning Cell - Yahaya, Muhammad Rasyidin (Universiti Sains Malaysia, 2017)
The study investigates the secondary current distribution in a zinc electrowinning cell in order to improve and understand the uniformity the current distribution via computational modeling. The research used COMSOL Multiphysics software as powerful tools in simulating the current distribution in a zinc electrowinning cell. The purpose of the study is to investigate the impact on the current distribution when operational and design parameter are varied. The study used different parameters in order to see the pattern changes when adding or reducing the value of the parameters. For the current distribution, some parameters have been used such as interelectrode space, thickness of anode, insulating edge strip, cathode displacement and temperature. Based on the simulation, parameter above shows positive impact to the uniformity of current distribution.